2020
DOI: 10.29169/1927-5951.2020.10.03.5
|View full text |Cite
|
Sign up to set email alerts
|

Issues of Type 2 Diabetes Disease Effective Treatment in Kazakhstan

Abstract: In his address to the people, the First President of our country, emphasized the need to introduce innovative methods of treating socially significant diseases. Among these diseases, diabetes holds a special position. More than 14,000 new cases of diabetes mellitus are officially detected annually in Kazakhstan.The real picture of the disease is difficult to compare with these data. This review discusses the prevalence of type 2 diabetes among the population of the Republic of Kazakhstan, and the causing facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Furthermore, it is expected that by 2030, this number in Kazakhstan will increase to 800,000 [ 3 ]. This is just one example of the global trend of a 2.5-fold increase in the number of DM patients over 10 years [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is expected that by 2030, this number in Kazakhstan will increase to 800,000 [ 3 ]. This is just one example of the global trend of a 2.5-fold increase in the number of DM patients over 10 years [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the issues of gerontology have moved from a medical problem to a problem of national importance. The upward trend in the number of older people requires a deep study of demographic processes and, first of all, the problems of older people [1].…”
Section: Introductionmentioning
confidence: 99%
“…The total number of registered cases of type 2 diabetes in Kazakhstan was 326.5 thousand in 2018 representing a substantial burden for the health care system, but the authors acknowledge that the real numbers can be even greater [19]. Ablaikhanova et al have reported a clear North-South gradient in the disease occurrence and expected the total number of people with diabetes in Kazakhstan to reach 1 million by 2030 [4].…”
Section: Introductionmentioning
confidence: 99%